ANALISIS PENYEBAB DAN SOLUSI KESULITAN BELAJAR MATEMATIKA SISWA SD: KAJIAN NARRATIVE LITERATURE REVIEW - Citra Ramadhani; Nadya Martasya; Masniladevi (Prodi PGMI STAI Sabili Bandung, 2026)
Learning difficulties in elementary school students are the most common problem encountered in the teaching and learning process, especially in mathematics. This problem not only impacts student learning outcomes but also influences student behavior and motivation towards learning mathematics. This study aims to identify and analyze the factors that cause learning difficulties and the efforts that can be made to overcome learning difficulties. The method used in this study is a Narrative Literature Review by reviewing literature relevant to the topic of study within the last 5 years. The articles used in the study are nationally accredited articles obtained from Semantic Scholar and Google Scholar using Publish Or Perish. The results of the study indicate that learning difficulties often experienced by students when learning mathematics are caused by internal and external factors. Internal factors originate from the student themselves such as attitudes in learning, motivation and interest, and health conditions. Meanwhile, external factors originate from the student's environment such as learning media, teaching methods used by teachers, infrastructure, friendships, and family support. From these problems, several efforts are formulated as solutions to the problem of learning difficulties in mathematics in elementary school students.